Epigenetic reprogramming and small RNA silencing of transposable elements in pollen - Slotkin, R.K. (2009)
The mutagenic activity of transposable elements (TEs) is suppressed by epigenetic silencing and small interfering RNAs (siRNAs), especially in gametes that could transmit transposed elements to the next generation. In pollen from the model plant Arabidopsis, we show that TEs are unexpectedly reactivated and transpose, but only in the pollen vegetative nucleus, which accompanies the sperm cells but does not provide DNA to the fertilized zygote. TE expression coincides with downregulation of the heterochromatin remodeler decrease in DNA methylation 1 and of many TE siRNAs. However, 21 nucleotide siRNAs from Athila retrotransposons are generated and accumulate in pollen and sperm, suggesting that siRNA from TEs activated in the vegetative nucleus can target silencing in gametes. We propose a conserved role for reprogramming in germline companion cells, such as nurse cells in insects and vegetative nuclei in plants, to reveal intact TEs in the genome and regulate their activity in gametes